Human exposure to chromite mining pollution, the toxicity mechanism and health impact - Changaiz Khan; Riffat Naseem Malik; Jing Chen (Heliyon)
Significant amounts of toxic metal-containing mining waste are produced by chromium mining activities, along with the production of air pollutants. The presence of toxic metals in various environmental media including air, water, and soil, along with their chemical species such as hexavalent chromium, pose major health hazards for both directly exposed mining workers and the population residing near the mining areas. Highlighting the requirements for enhanced environmental protection and safety measures, this comprehensive review shed light on the global environmental pollution stemming from chromite mining activities. Based on the published literature, the study also investigated into the pollution caused by toxic metals and explored their probable health effects on exposed individuals. The exposure routes and the mechanisms of toxic metal induced carcinogenicity in the exposed groups were assessed. Additionally, the generated reactive species in exposed individuals and the toxicity mechanisms of hexavalent chromium were discussed. Considering these findings, this review proposed the necessity of cross-sectional biomonitoring studies involving occupationally exposed workers from chromite mining operations. The anticipated impact of this review is to influence the global and national chromite mining industry, instigating improvements in occupational settings, real-time pollution monitoring, and healthcare provisions for exposed workers.